2021
DOI: 10.3928/01913913-20210128-01
|View full text |Cite
|
Sign up to set email alerts
|

Spot Refractive Screening With or Without Maximum Atropine Cycloplegia in Preschool Chinese Children

Abstract: Purpose: To evaluate averaged, repeat Spot Vision Screener (Welch Allyn) refractive screening with and without maximal atropine cycloplegia in preschool Chinese children. Methods: Refractive errors of 450 preschool children aged 3 to 6 years were measured by cycloplegic retinoscopy as the gold standard. The Spot Vision Screener was used to examine the refractive errors of these children before and after cycloplegia. The differences between the two metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The difference would also increase with increasing hyperopia. ( Doherty et al, 2019 ; Liu et al, 2021 ) As anterior segment changes are correlated with SE changes, greater SE changes may lead to greater anterior segment changes. For another thing, tropicamide may have weaker cycloplegic effects on hyperopic eyes compared to other mydriatics.…”
Section: Discussionmentioning
confidence: 99%
“…The difference would also increase with increasing hyperopia. ( Doherty et al, 2019 ; Liu et al, 2021 ) As anterior segment changes are correlated with SE changes, greater SE changes may lead to greater anterior segment changes. For another thing, tropicamide may have weaker cycloplegic effects on hyperopic eyes compared to other mydriatics.…”
Section: Discussionmentioning
confidence: 99%
“…If the difference between any of two readings from an eye was >0.5 diopters (D), re-measurement was conducted for that eye. Cylinder values and interocular difference of spherical equivalent were used for analysis of astigmatism and anisometropia, respectively, since it has been reported that astigmatism has no significant association with cycloplegia ( 8 ), and that Spot Vision Screener was efficient in detecting anisometropia ( 10 ). Besides, corneal light reflex and cover-uncover tests, near and at a distance, to detect strabismus, as well as slit-lamp examination to examine the eyelids, cornea, and lens, were conducted.…”
Section: Methodsmentioning
confidence: 99%
“…com) is a device that is often used for screening refractive errors without cycloplegia, 7,8 although it may underestimate spherical hyperopia. 9 Errors in screening refractive errors are larger in children with higher amounts of hyperopia, where differences of up to 4.00 D may be found. 9,10 Therefore, it is particularly important to evaluate the error in data derived from communitybased screening without cycloplegia.…”
mentioning
confidence: 99%
“…9 Errors in screening refractive errors are larger in children with higher amounts of hyperopia, where differences of up to 4.00 D may be found. 9,10 Therefore, it is particularly important to evaluate the error in data derived from communitybased screening without cycloplegia.…”
mentioning
confidence: 99%
See 1 more Smart Citation